Analisis Penerapan Konsep 4C dalam Pemasaran Digital di Industri E-Commerce Indonesia - Dewi Ayu Wardhani; I Made Rai Wiana; Maulana Rifky Ferdiansyah; Raida Namira; Izza Ahmad Muharis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The rapid development of digital technology has significantly transformed the modern marketing paradigm from a product-oriented to a consumer-oriented approach. This study aims to analyze the transformation of the traditional marketing mix concept of 4P (product, price, place, promotion) into the 4C framework (consumer, cost, convenience, communication) within the context of digital marketing in Indonesia. A descriptive quantitative method was employed, using secondary data obtained from industry reports, digital surveys, and observations of marketing strategies in the e-commerce sector. The findings reveal that companies adopting the 4C approach experience a substantial increase in marketing communication effectiveness and customer loyalty. Observation data indicate that 75% of digital-based companies implementing the 4C model recorded higher customer engagement, while 68% of consumers preferred platforms offering accessibility and personalized experiences. The analysis further shows that the shift from nominal pricing to experiential value enhances customer satisfaction and competitive advantage. These results affirm that the success of digital marketing strategies is not solely determined by product quality but also by the company’s ability to understand consumer needs, create value-driven interactions, and build sustainable communication in the digital ecosystem.